2021
DOI: 10.3389/fimmu.2021.676016
|View full text |Cite
|
Sign up to set email alerts
|

Review: The Nutritional Management of Multiple Sclerosis With Propionate

Abstract: Over the last 15 years there has been an accumulation of data supporting the concept of a gut-brain axis whereby dysbiosis of the gut microbiota can impact neurological function. Such dysbiosis has been suggested as a possible environmental exposure triggering multiple sclerosis (MS). Dysbiosis has been consistently shown to result in a reduction in short-chain fatty acid (SCFA) producing bacteria and a reduction in stool and plasma levels of propionate has been shown for MS patients independent of disease sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Propionate was previously identified to be significantly reduced in the serum of our CIS/MS cohort ( 18 ). Others have also identified low propionate levels in MS patients and supplementation alleviated their disease symptoms ( 36 ), as reviewed ( 37 ). In our study, the functions of circulating IgA + MBC were not analyzed and further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Propionate was previously identified to be significantly reduced in the serum of our CIS/MS cohort ( 18 ). Others have also identified low propionate levels in MS patients and supplementation alleviated their disease symptoms ( 36 ), as reviewed ( 37 ). In our study, the functions of circulating IgA + MBC were not analyzed and further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that SCFAs like propionate (PA) can promote polarization of naĂŻve CD4 + T cells into Tregs [139]. Administration of PA to a mice model of EAE showed an increased content of IL-10 together with a Treg cells' frequency showing a beneficial effect of PA on control of EAE symptoms [140], suggesting a key role for PA in restoring Treg/Teff cells balance, which has also been observed in MS patients [141][142][143]. Propionate has been suggested to have a regulatory role with regard to immune cells [144].…”
Section: Intestinal Microbiotamentioning
confidence: 93%
“…Hence, propionate could be potentially important in counteracting MS pathogenesis due to its modulation on the immune system [141]. There are some contradictory results regarding acetate levels, given that high levels of acetate in the plasma of MS patients is correlated with an expanded disability status scale and increased IL-17 + T cells [142]. On the other hand, Olsson et al (2021) demonstrated that low acetate levels in MS patients negatively correlate with IFN-Îł levels, while high butyrate levels positively correlate with pro-inflammatory cytokine levels [135].…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…39,40 Propionate has repeatedly been shown to be depleted in both the plasma and stool of MS patients, and supplementation of propionate slows MS disease progression. 41 Health-associated Hungatella hathewayi was also enriched post-FMT. 42 Recent evidence suggests a causal link between H. hathewayi depletion in MS patients and decreased serum taurine levels.…”
Section: Adverse Eventmentioning
confidence: 98%